Autobiographical memory and problem-solving strategies of parasuicide patients. - Evans, J; Williams, J; O'Loughlin, S; Howells, K (1992)
Recent research has noted the tendency of parasuicide patients to retrieve over-general autobiographical memories. Separate studies suggest problem-solving deficits within this group. The present study was concerned first with replicating these findings and, secondly, with developing a model of the relationship between over-general memory recall and poor problem-solving abilities in parasuicide patients. Anger and hopelessness were measured as markers for mood. In line with the hypotheses, the parasuicide group (N = 12) produced significantly over-general memories in contrast to a matched control group (N = 12). This occurred significantly in relation to positive cues, and latency to first responses was significantly delayed in the parasuicide group. The parasuicide group also provided fewer and less-effective problem-solving strategies than the control group, and a significant association was found between low effectiveness of problem-solving strategies and over-general memory recall in the parasuicide group. Anger and hopelessness levels were significantly higher within the parasuicide group in line with previous findings. The clinical implications of these findings are discussed.